Cyber security management of critical energy infrastructure in national cybersecurity strategies: cases of USA, UK, France, Estonia and Lithuania - Manuela Tvaronavičienė; Tomas Plėta; Silvia Della Casa; Juozas Latvys (Insights into Regional Development)
The progresses made in terms of cybersecurity in these past years have been huge, and the implementation of newer strategies has brought interesting results all over the globe. However, the full implementation of cybersecurity presents a challenge to a lot of countries, especially if considered the Critical Infrastructure Protection (CIP), which is still one of the areas with the most gaps in terms of cybersecurity. In this article, the first five countries by cybersecurity level according to the Global Cybersecurity Index (GCI) 2018, in order UK, USA, France, Estonia and Lithuania, will be evaluated for their solutions in terms of Critical Infrastructure Protection. The results will show the effective accuracy of the index and will shed light on the various approaches to Critical Infrastructure Protection.